Pulmonary availability of isotretinoin in rats after inhalation of a powder aerosol - Raleigh, S M (Nature Publishing Group, 2000)
Repeated oral administration of chemopreventive retinoids such as isotretinoin over extended periods of time is associated with intolerable systemic toxicity. Here isotretinoin was formulated as a powder aerosol, and its delivery to the lungs of rats was studied with the aim to explore the possibility of minimizing adverse effects associated with its oral administration. Rats received isotretinoin orally (0.5, 1 or 10 mg kg(–1)) or by inhalation (theoretical dose ~1 or ~10 mg kg(–1)) in a nose-only inhalation chamber. Isotretinoin was quantitated by high-pressure liquid chromatography in plasma and lung tissue. The ratios of mean area of concentration-vs-time curve (AUC) values in the lungs over mean AUCs in the plasma for isotretinoin following single or repeated aerosol exposure surpassed those determined for the oral route by factors of between two (single low-dose) and five (single high-dose). Similarly, the equivalent ratios for the maximal peak concentrations in lungs and plasma obtained after aerosol exposure consistently exceeded those seen after oral administration, suggesting that lungs were exposed to higher isotretinoin concentrations after aerosol inhalation than after oral administration of similar doses. Repeated high doses of isotretinoin by inhalation resulted in moderate loss of body weight, but microscopic investigation of ten tissues including lung and oesophagus did not detect any significant aerosol-induced damage. The results suggest that administration of isotretinoin via powder aerosol inhalation is probably superior to its application via the oral route in terms of achieving efficacious drug concentrations in the lungs. © 2000 Cancer Research Campaign